Subacute Toxicity Study of Nicotinamide Mononucleotide via Oral Administration - You, Yingnan; Gao, Yang; Wang, Han; Li, Jingshu; Zhang, Xiang; Zhu, Zhengjiang; Liu, Nan (Frontiers in Pharmacology, 2020)
Nicotinamide mononucleotide (NMN), a key precursory metabolite of NAD+, has been shown to elevate the cellular level of NAD+ and ameliorate various age-related diseases. Despite these progresses, systemic evaluation pertaining to the subacute toxicity of NMN remains to be determined. Here, we examine the subacute toxicity of NMN in mice and beagle dogs. Mice were gavaged with a saturated concentration of NMN solution at the maximum intragastric dose once or twice per day for 7 days. Dogs were gavaged twice per day for 14 days. In mice, NMN administrated once per day for 7 days is well tolerated with minimal deleterious effects. Upon higher dosage, we observe slightly increased level of alamine aminotransferase, while other biomarkers remain unchanged. Consistently, administration of NMN in beagle dogs only results in mild increases in creatinine and uric acid. Together, our study highlights the safety of NMN, providing a possible safe dose range for oral administration of NMN.